Image-based Glaucoma Classification Using Fundus Images and Deep Learning - Sandoval-Cuellar, Hiram José; Alfonso-Francia, Gendry; Vázquez-Membrillo, Miguel Ángel; Ramos-Arreguín, Juan Manuel; Tovar Arriaga, Saúl (Revista Mexicana de Ingenieria Biomedica, 2021)
Glaucoma is an eye disease that gradually affects the optic nerve. Intravascular high pressure can be controlled to prevent total vision loss, but early glaucoma detection is crucial. The optic disc has been a notable landmark for finding abnormalities in the retina. The rapid development of computer vision techniques has made it possible to analyze eye conditions from images enabling to help a specialist to make a diagnosis using a technique that is non-invasive in its initial stage through fundus images. We propose a methodology glaucoma detection using deep learning. A convolutional neural network (CNN) is trained to extract multiple features, to classify fundus images. The accuracy, sensitivity, and the area under the curve obtained using the ORIGA database are 93.22%, 94.14%, and 93.98%. The use of the algorithm for the automatic region of interest detection in conjunction with our CNN structure considerably increases the glaucoma detecting accuracy in the ORIGA database.